2004
DOI: 10.1099/vir.0.80160-0
|View full text |Cite
|
Sign up to set email alerts
|

The P gene of Newcastle disease virus does not encode an accessory X protein

Abstract: Many paramyxoviruses encode non-essential accessory proteins that are involved in the regulation of virus replication and inhibition of cellular antiviral responses. It has been suggested that the P gene mRNA of Newcastle disease virus (NDV) encodes an accessory protein -the so-called X protein -by translation initiation at a conserved in-frame AUG codon at position 120. Using a monoclonal antibody that specifically detected the P and X proteins, it was shown that an accessory X protein was not expressed in ND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
8
0
3
Order By: Relevance
“…15 mRNA cleavage might explain why upORFs which strongly inhibit translation in vivo are sometimes less inhibitory in vitro (Ghilardi et al, 1998;Meijer et al, 2000;Pecqueur et al, 2001;Tanaka et al, 2001) and why translation sometimes initiates in vitro at fardownstream AUG codons which are not used in vivo (Byrd et al, 2002, Fig. 3C;Hassin et al, 1986;Meulewaeter et al, 1992;Peeters et al, 2004). In vitro translation reactions that generate an array of low molecular weight polypeptides are a sure sign of mRNA degradation (e.g.…”
Section: Experimental Deficiencies Underlie Other Misunderstandings Amentioning
confidence: 96%
“…15 mRNA cleavage might explain why upORFs which strongly inhibit translation in vivo are sometimes less inhibitory in vitro (Ghilardi et al, 1998;Meijer et al, 2000;Pecqueur et al, 2001;Tanaka et al, 2001) and why translation sometimes initiates in vitro at fardownstream AUG codons which are not used in vivo (Byrd et al, 2002, Fig. 3C;Hassin et al, 1986;Meulewaeter et al, 1992;Peeters et al, 2004). In vitro translation reactions that generate an array of low molecular weight polypeptides are a sure sign of mRNA degradation (e.g.…”
Section: Experimental Deficiencies Underlie Other Misunderstandings Amentioning
confidence: 96%
“…It encodes at least six proteins: the nucleocapsid protein (N), the phosphoprotein (P), the matrix protein (M), the fusion protein (F), the hemagglutinin-neuraminidase protein (HN), and the large polymerase protein (L) (4,29). Two additional proteins, V and W, are produced by RNA editing during P gene transcription (21,27). The M, F, and HN proteins are associated with the virus envelope, and the latter two are the protective antigens of NDV.…”
mentioning
confidence: 99%
“…Consequently, during translation there is a frame shift resulting in production of the V or W protein, dependent on the number of G nucleotides inserted [12]. It was previously suggested that NDV [26] potentially utilized an alternative in-frame AUG start site for expression of an accessory protein similar to the Sendai virus X protein [21] that was recently demonstrated to not be utilized during infection of cells in culture [27]. …”
Section: Discussionmentioning
confidence: 99%